Case report of a patient with acute renal failure and cardiovascular disease after 65 years of age - Anna Ziółkowska; Paulina Kasperska; Eliza Oleksy; Paweł Wojtczak; Karolina Klimkiewicz-Wszelaki; Remigiusz Sokołowski; Walery Zukow; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Introduction. Acute kidney injury (AKI) is a clinical syndrome with high mortality. It is a clinical syndrome consisting in rapid impairment of kidney function. The result is retention of metabolic products in the body and the inability to maintain normal water-electrolyte and acid-base homeostasis. Chronic heart failure is a significant clinical, economic and social problem, and despite the continuous development of medicine, the incidence of this disease is still increasing. A weakened inefficient heart is not able to supply the organs with the right amount of blood, oxygen and nutrients. The effect is fast fatigue, weakness of muscle strength and dizziness. Kidney and cardiovascular diseases affect each other and increase their course, which worsens the patient's condition. Periodic monitoring of renal function in patients with cardiovascular disease is very important because it has been proven that the occurrence of kidney disease in these patients increases the risk of death. Case report. Patient, 78 years old, hospitalized many times in the Geriatrics Clinic, Cardiology Clinic, Nephrology Clinic due to shortness of breath, chronic myocardial insufficiency, edema of the lower limbs. The degree of independence is limited, the patient walks with assistance, lives with a family / significant other. Main ailments of the patient: increasing swelling of the lower limbs, left foot pain, nausea, vomiting, palpitations, effortlessness and rest dyspnea without stenocardial complaints. Comorbidities: Type 2 insulin-dependent diabetes mellitus (with unspecified complications), obesity, generalized atherosclerosis, hypertension, chronic NYHA type II heart failure. Cardiac defect in the form of mitral and tricuspid regurgitation, pulmonary hypertension, paroxysmal atrial fibrillation, myocardial infarction. The patient was qualified for hemodialysis treatment, then returned to conservative treatment, followed a strict diet. The applied treatment improved the general condition of the patient and was discharged from the hospital in a stable general condition. Results. Frequent and regular examination of a patient's condition with cardiac-renal syndrome, disease progression and ability to tolerate treatment can be helpful in treating and prolonging the patient's life. It is important to monitor kidney function in people with cardiovascular disease.